The effectiveness of think-pair-share model in the reading class among tenth-graders of vocational high school students - Didik Rinan Sumekto (Research and Social Study Institute, 2025)
This study aims at assessing the tenth-graders’ reading achievements at the Vocational High School whose organizationally affiliates with Muhammadiyah Islamic organization in Seyegan Sleman through the think-pair-share model. Thirty-six (n = 36) students of tenth-graders of the vocational high school participated as the respondents. Data collection used tenth-graders’ reading test and learning observation. Quantitative data were statistically analyzed by the SPSS program to gain the descriptive analyses of the test, while qualitative data analyzed by qualifying the observational-based session descriptively. The finding of the test also noted that the lowest score of reading gained 45.00 and the highest score was 100.00 through the analytic scoring assessment. Meanwhile, the mean was 78.89 and the standard deviation was 14.289 (n = 36). The overall achievement of reading was in good category with 25.0%, while the finding of the observation showed that the tenth graders were able to work with their friends in reading class by conducting the think-pair-share model.